EFFECTIVE PHYSIOTHERAPEUTIC APPROACH FOR BELL’S PALSY: A PRELIMINARY STUDY OF A TAILORED APPROACH - Dr. P.R. Suresh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Bell's palsy is a unilateral facial paralysis caused by malfunction of the face nerve (cranial nerve VII). This case study analyzes the rehabilitation of a 34-year-old female patient diagnosed with Bell's palsy, utilizing a specialized physiotherapeutic program for six weeks. The regimen included face exercises, manual therapy, and neuromuscular electrical stimulation (NMES). Post-test evaluations were performed biweekly to examine face symmetry, muscular strength, and overall functional improvement. The results demonstrated substantial enhancements in face muscle function and patient-reported outcomes, signifying the efficacy of the tailored rehabilitation program.